Strategi Guru Dalam Menanamkan Interpersonal Skill Peserta Didik Pada Pembelajaran Sejarah di Kelas XI IPS SMA Katolik Sungai Ambawang - septiani, angela; Chalimi, Ika Rahmatika; Firmansyah, Haris (Peneliti.net, 2025)
Humans play an important role as the main character in maintaining the stability of relationships in the social sphere. Students will later face the reality that exists in the social sphere so that it is important to build interpersonal skills in students. This study aims to determine the teacher's strategy in instilling interpersonal skills in students which will be carried out through history learning in class XI of SMA Katolik Talino Sungai Ambawang. This study uses a qualitative research type with a case study approach. Data collection includes interviews, documentation and observations where the interviews were conducted with teachers and also class XI students. The stages in data analysis consist of data collection, reduction, presentation and conclusions. The validity of this data uses source triangulation and technique triangulation. The results of the study show: First, there are 5 aspects in analyzing students' interpersonal skills, namely having the ability to take the initiative, an open attitude, an assertive attitude, providing emotional support and resolving conflicts. Second, there are two influencing factors, namely external factors originating from the family and school environment and internal factors originating from the individual (intelligence, personality and physical condition). Third, the role of history teachers in building interpersonal skills is to provide discussion space, form groups and maximize RPP. So it is concluded that instilling interpersonal skills in students starting from the surrounding environment such as emotional support from family and also school is the role of teachers in maximizing RPP so that interpersonal skills can be honed